Changes in the Etiology of Endophthalmitis from 2003 to 2010 in a Large Tertiary Medical Center. Issue 6 (November 2014) - Kessner, Rivka; Golan, Shani; Barak, Adiel
Purpose: To ascertain the leading causes of endophthalmitis at the Tel Aviv Medical Center between 2003 and 2010. Methods: The design of the study is retrospective chart review. The medical records of all patients diagnosed with endophthalmitis in our center between 2003 and 2010 were reviewed for visual acuity and results of ophthalmologic examination at admission, treatment, complications, laboratory investigations, and final visual results. The etiologies of endophthalmitis after cataract surgery were compared for each year from 2003 to 2010, and after intravitreal (IVT) injection from 2006 to 2010. Results: Eighty patients were diagnosed with endophthalmitis between 2003 and 2010: 46 male and 34 female, average age 70.7 years. A total of 27.5% were treated with IVT antibiotic injection only and 68.8% needed pars plana vitrectomy. Final visual acuity was better than counting fingers in 56.3% of cases. Surgery was almost the sole cause of endophthalmitis until 2005, when IVT injection became an important etiology. The incidence of postcataract endophthalmitis decreased significantly after 2007 and that following IVT injection decreased significantly after 2008. Conclusions: The leading etiology of endophthalmitis changed from postoperative endophthalmitis to endophthalmitis after IVT injection from 2003 to 2010, and the incidence of the infection as a complication of those procedures decreased.